PAI AS A COUNTER-NARRATIVE IN THE POST-TRUTH ERA: A LITERATURE STUDY ON DEVELOPING CRITICAL DIGITAL LITERACY AMONG STUDENTS - Ummu Khairin Nisa; Rega Armela (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The post-truth era has presented significant challenges for the world of education, especially in the context of Islamic Religious Education (PAI), because the strong dominance of emotions and subjective opinions over objective facts makes it easier to spread misinformation and disinformation among students. This article aims to conduct a methodical study on how PAI can be utilized as a strategic counter-narrative in an effort to develop students' critical digital literacy to face the challenges of the post-truth era. This research uses a descriptive qualitative method with an integrative literature review design, using thematic analysis techniques. The research findings show that PAI has important epistemological and pedagogical potential as a counter-narrative through strengthening the values of tabayyun, amar ma'ruf nahi munkar, justice, and honesty that are relevant to critical digital literacy. Effective strategies include the application of critical pedagogy, the use of authentic media, problem-based learning (PBL), project-based learning (PJBL), and interdisciplinary collaboration. In conclusion, the integration of critical digital literacy in PAI learning can equip students with evaluative critical thinking skills, moral responsibility, and cognitive resistance to hoaxes and religious propaganda, in addition to demanding educational policies and teacher training that support sustainable implementation.